In-stent restenosis of drug-eluting stents in patients with diabetes mellitus: Clinical presentation, angiographic features, and outcomes - Ganesh Paramasivam; Tom Devasia; Ashwal Jayaram; Abdul Razak U.K; M. Sudhakar Rao; Rajesh Vijayvergiya; Krishnananda Nayak (Anatolian Journal of Cardiology)
Objective: Diabetes mellitus (DM) is a risk factor for developing in-stent restenosis (ISR) following percutaneous coronary intervention (PCI). This study aimed to examine the presentation and outcomes of drug-eluting stent (DES) ISR in diabetics. Methods: This retrospective study included consecutive patients with clinical DES-ISR, who were hospitalized between January 2013 and December 2017 and who were grouped based on the presence or absence of DM. Clinical, angiographic features and 1-year outcomes [composite of death, myocardial infarction (MI), and repeat-target lesion revascularization] were compared. Results: Baseline characteristics of the DM group (n=109) were comparable to the non-DM group (n=82), except for the higher prevalence of hypertension and dyslipidemia in the former (60.6% vs. 46.3%, p=0.050; 74.4% vs. 57.8%, p=0.034, respectively). Clinical presentation was similar in both groups [acute coronary syndrome (ACS): 62.4% vs. 61%, p=0.843; MI: 34.9% vs. 34.1%, p=0.918). Diabetics had a higher prevalence of stent-edge restenosis (20.3% vs. 9.2%, p=0.019). The treatment strategy was similar in both groups with 52.3% in the DM group and 57.3% in the non-DM group undergoing PCI (p=0.513). One-year outcomes of the DM group were not different from those of the non-DM group (14.7% vs. 17.1%, p=0.683). Age [hazard ratio (HR), 1.05; 95% confidence interval (CI), 1.01–1.10; p=0.017], MI presentation (HR, 2.34; 95% CI, 1.14–4.80; p=0.020), and chronic kidney disease (CKD: HR, 2.82; 95% CI, 1.21–6.58; p=0.016) were predictors of poor outcomes. Conclusion: Stent-edge restenosis is more common in diabetics. Clinical presentation and 1-year outcomes following DES-ISR are similar in diabetics and non-diabetics. Age, MI presentation, CKD, and not DM were predictors of poor outcomes following DES-ISR.